Vertical Motion Optimization of Series 60 Hull Forms Using Response Surface Methods - Utomo, Budi; Iqbal, Muhammad (Department of Naval Architecture - Diponegoro University, 2020)
There are many aspects to analyze seakeeping performance, one of which is the ship's vertical motion. As well-known, vertical motion and its derivatives, vertical velocity and acceleration, will be related to other aspects of seakeeping performance, such as slamming, deck wetness, and MSI. This study discusses optimizing the hull shape with small vertical motion using the Response Surface Methods (RSM). This research aims to minimize the ship's vertical motion so that the ship's performance is better than the initial one. Besides, this research was conducted to apply the RSM in the naval architecture field. The hull's shape used in this study is Series 60 hull form with a length of 31 m. The variables used for the optimization process are the ratio of L/B (X1) and B/T (X2) in the range of Â± 10% with fixed displacement. Seakeeping analysis was carried out at a speed of 6.78 knots (Fr 0.2), a heading angle of 180Â°, and a significant wave height of 0.77 meters. The results show that the optimum model is found in Model 9 where the value of X1 = -2.94 or L/B = 6.71 and X2 = 5 or B/T = 2.75. Model 9 can reduce the vertical motion of the ship by 16.38%.